SOME PHYSICAL AND TECHNICAL PARAMETERS OF PYROGRAPHITE - Skachkov , Viсtor; Ivanov , Victor; Nesterenko , Tatiana; Berezhnaya , Olga (Scientific Journal "Metallurgy", 2020)
The row of physical and technical parameters for volume and laminar pyrographite is studied. Influence of flowrates of reaction gases in the deposition process for pyrographite on speed of its height, interplanar spacing and height of crystallines is set, and also influence microstructure deformations, interplanar spacing and height of crystallines on tensile of pyrographite strength on a bend is set. On the diffractometer of ДРОН-2У (determined interplanar spacing the method of X-ray analysis, height of кристалітів and also level of remaining microstructure deformations (hall. interplanar spacing d002 was calculated with the use of BreggVulf/ Sizes of crystallines of pyrographite determined with the use Selyakov-Sherrer formulas. By the methods of mathematical statistics equation of regression of dependence of border of durability on the bend of pyrographite (In from x-ray and mechanical descriptions is got. Regressive equation which determines the level of remaining microstructure deformations (hall can be given as a quadratic polynomial. Researches of триботехнічних descriptions of pyrographite in the conditions of dry friction carried out on a chart shoe "disk- tree". Disk with diameter a 50 mm made from grey cast-iron, the samples of both types of pyrographite executed, taking into account their anisotropy, as a shoe tree by the sizes of 16х10х11 mm. Direction of plane of friction in relation to the surface of deposition folded 0, 45 and 90 angular degrees. The maximal value of coefficient of friction answers a slickenside which is directed athwart to the surface of deposition. In this direction of pyrographite does not have the lubricating opportunity that it is caused by the change of datum carbon planes in relation to each other. For slickensides, that it is located under the corner of 45 (, possibility appears for the change of separate base carbon surfaces. interplanar durability in pyrographite is practically compared to the level of remaining tensions. Appearance of force of friction, which is directed in parallel or under a small corner to the base carbon layers, creates the terms of their tearing away on separate microsections, and also predetermines appearance of the phenomenon of self-lubricating and decline of coefficient of friction practically in 2,0-2,5 times. In the case of running back of slickenside with the surface of deposition of pyrographite the mechanism of самозмащування and coefficient of friction will be realized has a minimum value.